2016
DOI: 10.1039/c6cp07092b
|View full text |Cite
|
Sign up to set email alerts
|

White polymer light emitting diodes based on PVK: the effect of the electron injection barrier on transport properties, electroluminescence and controlling the electroplex formation

Abstract: The effects of the electron injection barrier on the charge transport, brightness and the electroluminescence (EL) properties of polymer light emitting diodes (PLEDs) with poly(9-vinylcarbazole) (PVK) as an emissive layer have been studied. By using Al and LiF/Al as the cathode in single layer PLEDs and diverse electron transporting layers (ETLs) such as 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP), 4,7-diphenyl-1,10-phenanthroline (BPhen) and 2,2',2''-(1,3,5-benzinetriyl)-tris(1-phenyl-1-H-benzimidazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…From these results, it has been observed that the devices with TPBi as ETL exhibited improved brightness and lowered turn on voltage as compared to the devices with BPhen as ETL. This is due to the lower electron injection barrier of TPBi‐PVK interface that facilitates more electron injection into the emissive layer resulting in an increased recombination at a comparatively lower voltage …”
Section: Methodsmentioning
confidence: 99%
“…From these results, it has been observed that the devices with TPBi as ETL exhibited improved brightness and lowered turn on voltage as compared to the devices with BPhen as ETL. This is due to the lower electron injection barrier of TPBi‐PVK interface that facilitates more electron injection into the emissive layer resulting in an increased recombination at a comparatively lower voltage …”
Section: Methodsmentioning
confidence: 99%
“…These results may be attributed to the deeper HOMO and LUMO energy levels of OXD-7, which may act as trap center for the injected holes and may cause unnecessarily excess electron injection in to the emission layer, respectively. Hole mobility values of PVK:PBD and PVK:OXD-7 hosts are calculated to be 2 × 10 −6 and 8 × 10 −7 cm 2 V −1 s −1 , whereas the electron mobility values are 8.7 × 10 −7 and 1.1 × 10 −5 cm 2 V −1 s −1 , respectively [25], OXD-7 [34], PBD [35], are taken from literature and PTE and PDI are calculated by using the first reduction potentials and optical band gaps (Figure S2)] and cross sectional view of fabricated device.…”
Section: Characterization and Determination Of Host Matrixmentioning
confidence: 98%
“…Figure 1. Energy band diagram of the devices, chemical structure of PTE and PDI [energy levels of PVK[25], OXD-7[34], PBD[35], are taken from literature and PTE and PDI are calculated by using the first reduction potentials and optical band gaps (FigureS2)] and cross sectional view of fabricated device.…”
mentioning
confidence: 99%
“…As shown in Fig. 9, the devices with ETLs BCP and/or BPhen gave close to white light emission with (0.30, 0.30) and (0.25, 0.23) as CIE values at 20 V [27].
Fig.
…”
Section: Woleds Based On Blending Approach and Exciplex Formationmentioning
confidence: 99%
“…9 a The EL spectra and b the CIE co-ordinates diagram of the undoped PVK based PLEDs with or without different ETLs (DEV B-without ETL, DEV B-BCP, DEV B-Bphen and DEV B-TPBi)(Reproduced with permission from Ref. [27] Copyright 2016, ©Physical Chemistry Chemical Physics)…”
Section: Woleds Based On Blending Approach and Exciplex Formationmentioning
confidence: 99%